The potential for silk in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Silk production is typically associated with Asia, where silk processing was first developed over 4,500 years ago in China. The growing demand for silk in recent years has created opportunities for silk production in other parts of the world,...